PENJAROAN RAJAB IN SAKATUNGGAL MOSQUE AT CIKAKAK VILLAGE: A STUDY OF LOCAL WISDOM - Novita Siswayanti (Jurnal Dialog, 2018)
English This paper attempts to describe how local wisdom is maintained in the ceremony of Penjaroan Rajab in Sakatunggal Mosque, Cikakak Village. The research was conducted using qualitative method with anthropological and historical approaches. This study is to identify the contestation of local wisdom in community ceremonies of Penjaroan Rajab where values are strongly planted in the community behavior, religious systems and beliefs. It finds that Penjaroan Rajab is a grave visit ritual that is conducted every 26th of the month of Rajab as a symbol of respect to the deceased Kiai Mustholih (the founder of the village). This ritual is marked by the replacement of fences surrounding the graveyard, slametan ngalap berkah (ritual meal to invoke blessing), Islamic sermons, and cultural performances. This ritual preserves the local wisdom of the Cikakak community including sincerity, harmony, religiosity and nationalism that melt people from different places and religions into the color of togetherness. Indonesia Artikel ini berupaya mendeskripsikan kearifan lokal yang ada pada ritual Penjaroan Rajab di Masjid Saka Tunggal Desa Cikakak. Penelitian dilakukan dengan metode kualitatif dengan pendekatan antropologis dan historis. Penelitian untuk mengidentifikasi kearifan lokal pada ritual Penjaroan Rajab melalui nilai-nilai yang terdapat pada perilaku masyarakat, sistem agama dan kepercayaan. Hasil penelitian ini menunjukkan bahwa Penjaroan Rajab adalah ritual ziarah kubur setiap tanggal 26 Rajab sebagai simbol penghormatan kepada leluhur Kiai Mustholih. Ritual ini ditandai dengan penggantian pagar yang mengelilingi pemakaman, slametan ngalap berkah, pengajian, dan pentas budaya. Ritual ini melestarikan kearifan lokal masyarakat Cikakak meliputi keikhlasan, kerukunan, keberagamaan, dan nasionalisme sebagai elemen perekat lintas warga dan lintas agama yang memberikan warna kebersamaan.